A COMPREHENSIVE STUDY ON THE DEVELOPMENT OF AN AUTOMATED RFID-BASED SECURITY SYSTEM FOR RESIDENTIAL AND INDUSTRIAL APPLICATIONS - Rao, Alwal Keerthan; Reddy, T. Rajashekar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The project's objective is to develop a fully automated security access system for both household and industrial use. Security is a key concern for both individuals and firms. In response to the demand for security, we have created an automated security access system that is easy for users to navigate. Automation is the most commonly written word in the domain of electronics. The need for automation has sparked numerous technological breakthroughs. RF communications is one of the technologies that has experienced significant advancements. The outcome of this process is the production of RFID cards that transmit a distinct identifying number. The RFID number can be detected using an RF reader. The level of access to the house or industry might be granted in its entirety or restricted based on the RFID cards. The determination of granting either full access or limited access is made by an onboard computer that is connected to the RF reader. The doors of the house/industry serve as the output module and are connected to the onboard computer via a motor. This onboard computer has a variety of input and output ports. The word typically used to refer to the onboard computer is microcontroller. The controller's input and output ports are connected to various input and output modules based on specific needs. Put simply, the microcontroller serves as a means of communication amongst all the modules in the project. The device is equipped with an LCD screen that provides information regarding the status of the doors, whether they are open or closed.